The impacts of suppliers and mutual outsourcing on organizational forms - Yasuhiro Arai; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We consider a downstream duopoly model with a monopolistic common supplier and mutual outsourcing between the two symmetric downstream firms. The market structure captures the recent procurement environment in the smartphone industry. We also incorporate managerial delegations into the duopoly model because deciding on organizational forms within a firm is critical to achieving better performance in almost all industries. There is an equilibrium in which only one of the firms delegates its downstream production to its sales manager. A delegating firm becomes less aggressive. The profits when both firms delegate can be higher than those when no firm delegates. The total surplus when both firms delegate is smaller than that when no firm delegates.
Keywords: L13; D43; 330; Mutual outsourcing; Supplier; Delegation; Asymmetric managerial forms